Evaluation of nutritive quality of fungal-treated cereal straw and further modification of Karnal process - SINGH, G P; GUPTA, B N (The Indian Journal of Animal Sciences, 2013)
Nutritive quality index Was developed to compare the nutritive quality offungal biomass along with some common forages. Two-stage Karnal process.of Coprinus treatment of straw was further modified by using anhydrous ammonia for first stage treatment of wheat and paddy straws to reduce the totd period for preparation of fungal biomass without affecting the quality of biomass. Nutritive quality index (NQI) of fungal-treated wheat straw was comparable with maize fodder and NQI of fungal-treated paddy straw was almost equal to oat fodder and higher than green maize. Results of modified Karnal process indicated that the increase in true protein was almost similar to the fungal biomass prepared through urea treatment followed by Coprinus fimetarius inoculation. Increase in amino acids content was from 1.54 times (histidine) to 39.79 times (arginine), and 4.35 times (arginine) to 35.25 times (methionine) higher in Coprinus-treated wheat and paddy straw. respectively. than untreated one. Total period offungal treatment of straw through 2-stage Karnal process was reduced to 12 days (7+5 days) from 35 days (30+5 days).